2021
DOI: 10.1177/1550147721993403
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic service migration strategy based on mobility prediction in edge computing

Abstract: Mobile edge computing is a new computing paradigm, which pushes cloud computing capabilities away from the centralized cloud to the network edge to satisfy the increasing amounts of low-latency tasks. However, challenges such as service interruption caused by user mobility occur. In order to address this problem, in this article, we first propose a multiple service placement algorithm, which initializes the placement of each service according to the user’s initial location and their service requests. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In comparison with existing MDP-solving algorithms, the author claims that the proposed algorithm is more efficient. In [14] the L.Rui, S.Wang et al suggested a dynamic knowledge service placement and migration scheme in edge networks (DSM), which initializes each service's placement based on the first position and service requests of the users that meet their needs. The simulation results display the dynamic service migration approach increases mobile edge computing's service efficiency in the user's mobile scene compared to the conventional scheme.…”
Section: Related Workmentioning
confidence: 99%
“…In comparison with existing MDP-solving algorithms, the author claims that the proposed algorithm is more efficient. In [14] the L.Rui, S.Wang et al suggested a dynamic knowledge service placement and migration scheme in edge networks (DSM), which initializes each service's placement based on the first position and service requests of the users that meet their needs. The simulation results display the dynamic service migration approach increases mobile edge computing's service efficiency in the user's mobile scene compared to the conventional scheme.…”
Section: Related Workmentioning
confidence: 99%